2012
DOI: 10.1021/la303037d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Attraction between Silanated Silica Surfaces in the Absence of Bridging Bubbles

Abstract: The interaction forces between silanated silica surfaces on which there were neither nanobubbles nor a gas phase were measured using colloidal probe atomic force microscopy (AFM). To obtain hydrophobic surfaces without attached nanobubbles, an aqueous solution was introduced between the surfaces after an exchange process involving several solvents. In the approaching force curves obtained, an attractive force was observed from a distance of 10-25 nm, indicating the existence of an additional attractive force s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 73 publications
4
28
0
Order By: Relevance
“…Lou et al (2000Lou et al ( , 2002, Zhang, Maeda, and Craig (2006) flow rate influences the concentration gradient of ethanol and hence the transit saturation level of the gas, as the solubility of atmospheric gases decreases (nonlinearly) with the decrease of ethanol concentration in water (Pollack, 1991). In case that the exchange was performed stepwise, that is, ethanol was replaced subsequently by an ethanol aqueous solution of 80%, 60%, 40% etc., no nanobubbles formed on the surface (Ishida, Kusaka, and Ushijima, 2012). The mixing pattern is also related to the shear on the surface.…”
Section: Mixing Flowmentioning
confidence: 93%
See 1 more Smart Citation
“…Lou et al (2000Lou et al ( , 2002, Zhang, Maeda, and Craig (2006) flow rate influences the concentration gradient of ethanol and hence the transit saturation level of the gas, as the solubility of atmospheric gases decreases (nonlinearly) with the decrease of ethanol concentration in water (Pollack, 1991). In case that the exchange was performed stepwise, that is, ethanol was replaced subsequently by an ethanol aqueous solution of 80%, 60%, 40% etc., no nanobubbles formed on the surface (Ishida, Kusaka, and Ushijima, 2012). The mixing pattern is also related to the shear on the surface.…”
Section: Mixing Flowmentioning
confidence: 93%
“…The solvent exchange process has meanwhile successfully been applied in many research groups to produce surface nanobubbles; see, e.g., Martinez and Stroeve (2007), S. Yang et al ( , 2008, Hampton, Donose, and Nguyen (2008), Palmer, Cookson, and Lamb (2011), Chan and Ohl (2012), Ishida, Kusaka, and Ushijima (2012), Karpitschka et al (2012), and Belova et al (2013). We discuss many of these papers later in this section and in Sec.…”
Section: Solution Bmentioning
confidence: 99%
“…Indeed, the hydrophobic attraction has been found between highly hydrophobic surfaces in the absence of nanobubbles or electrostatic attraction (Ishida et al, 2012), as shown in Fig. 9.…”
Section: Hydrophobic Attractionmentioning
confidence: 88%
“…CP-AFM is espe-cially useful in the investigation of the so-called hydrophobic effect or the occurrence of small gas layers on hydrophobic surfaces, the nanobubbles (more generally they are gas structures on partially wetted surfaces), responsible for the hydrophobic effect [15 -26]. There still is, however, some controversy in the science community about whether gas layers are only responsible for the long range hydrophobic effect [19,27]. It was emphasized by Heinrich Schubert that the hydrophobic effect caused by nanobubbles is, besides the hydrodynamics in a flotation cell, the most essential microprocess for separating minerals by flotation [28].…”
Section: Introductionmentioning
confidence: 99%